Reaproveitamento de sabugo de milho para potencial remoção de formulação comercial de glifosato em fase aquosa pela técnica de adsorção - Marcelino, Nayara Valéria Assis (2020)
Like the chemical industries applied to agriculture and livestock, they develop several chemicals for use in the environment, including chemicals that can be used for endocrine disrupting activities. In this context, the use of the herbicide Glyphosate (GLF), which is among the four most used agrochemicals in Brazil (glyphosate and its salts; 2,4-D; Acephate; mineral oil) is the main used, soybean and sugar cane. The main source of exposure of glyphosate to living organisms is a water intake, since water and wastewater treatment systems are not able to remove or degrade by a complete series of synthetic organic compounds. In this situation, it is necessary to use complementary treatment methods, of which adsorption may be of technical and environmental interest, due to its efficiency and, mainly, in the versatility of raw materials used for the production of material adsorbent. Thus, the objective of this study was the reuse of corn maize through the production of biochar (BC) and activated carbon (CA), for potential removal of glyphosate herbicide (GLF) (commercial use) in aqueous medium using the technique of adsorption. The BC was subjected to only the carbonization step, while the CA was subjected to carbonization followed by chemical activation with H3PO4. The adsorbents were characterized by X-ray diffraction (DRX) and infrared analysis by Fourier transform (FTIR), adsorption and N2 desorption, scanning electron microscopy (SEM) and determination of the zero charge potential (pHPCZ). The effect of the initial pH and the adsorbent mass was also evaluated. The kinetic studies of adsorption were adjusted to the models of pseudo-first and pseudo-second order. The nature of the adsorption process was studied using the Langmuir and Freundlich isotherm models, and the thermodynamic parameters calculated for the temperatures of 23, 43 and 63 ° C. The acid treatment caused an increase in the surface area (7.48 m² / g BC to 34.126 m² / g CA) favoring the formation of mesopores and had little influence on the surface loads. The adsorption of GLF proved to be highly dependent on pH and both adsorbents reached their maximum adsorption capacity at neutral pH (7.0). Both adsorbents reached equilibrium in 60 min of testing, and in just 15 min the CA reaches 93% of its maximum adsorption capacity and the BC 68%, showing a better fit to the pseudo-second model. indicating a tendency for chemical adsorption. The equilibrium data obtained experimentally, for temperatures of 23, 43 and 63 ° C, showed a better fit to the Langmuir model for the BC indicating chemisorption, and Freundlich for the CA indicating Fisissorection. Chemical activation increased the maximum adsorption capacity (Langmuir qmax) from 1.08 mg g-1 to 1.51 mg g-1 The values of the thermodynamic constants revealed that the adsorption of GLF is endothermic in nature, favored with the increase in temperature (ΔH> 0), and endergonic (ΔG> 0), indicating that the adsorption process is not spontaneous.